GAMBARAN MASSAGE BAYI SEHAT DAN TUMBUH KEMBANG PADA BAYI - Rahmi Nawiti; Sarah Fitria (Jurnal Ilmiah Kesehatan, 2024)
Baby massage is a massage carried out by touching and gently stroking or called tactile stimulation which is carried out on the surface of the skin, manipulating the tissues or organs of the body with the aim of producing an effect on the nerves, muscles and respiratory system as well as improving blood circulation in the baby. This research aims to find out why doing baby massage is very important for the baby's growth and development. This research also aims to motivate mothers who are still afraid to massage their babies themselves at home. Baby massage can express the love between parents and their children through skin touch which has a tremendous impact. This research uses the Pre-Experimental Design method, which is research with a serious experiment because there are still variables that are influenced by the formation of the dependent variable. The results of this research are that there is an influence of baby massage and baby growth and development at the Sejahtera clinic. Based on research conducted, there is an influence between baby massage and baby growth and development. The growth and development of babies is greatly influenced by several factors, including family income and a history of exclusive breastfeeding, where there is a tendency for mothers to have high incomes and breastfeed exclusively, which will tend to have good baby growth and development.